2015
DOI: 10.1589/jpts.27.3421
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-intensity laser therapy (LILT) on cutaneous wound healing and pain relief in rats

Abstract: [Purpose] This study examined the impact of low-intensity laser therapy on wound healing and pain control using a rat cutaneous wound model. [Subjects and Methods] Twenty-four adult male Sprague-Dawley rats (between 220−240 g, 7 weeks) were used in this study. The rats were anesthetized and a circular fragment of skin was removed from the dorsal region of the back by a punch with an 8-mm diameter. The animals were randomly divided into 6 groups, Groups C 1, C 3, and C 5, control groups, received no laser treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…LLLT is applied to reduce pain [28,29] and inflammatory conditions [14,30] and to accelerate bone growth [15,31] as well as wound and ulceration healing [13,32]. Research on LLLT as a method of preventing or alleviating delayed onset muscle soreness has started to be carried out only recently [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LLLT is applied to reduce pain [28,29] and inflammatory conditions [14,30] and to accelerate bone growth [15,31] as well as wound and ulceration healing [13,32]. Research on LLLT as a method of preventing or alleviating delayed onset muscle soreness has started to be carried out only recently [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recent years have seen an increased interest in the application of low-level laser therapy (LLLT) and lightemitting diode therapy (LEDT). There are numerous studies describing the effectiveness of LLLT and LEDT in wound healing [13], inflammation reduction [14], or bone healing [15]. It has been reported that LLLT may prove beneficial in preventing and reducing the intensity of delayed onset muscle soreness and may accelerate post-exercise recovery when applied shortly before training [16].…”
Section: Original Research Papersmentioning
confidence: 99%
“…The results of this study indicate that protein malnutrition has a negative effect on wound healing. The classic model of cutaneous healing adopted in this experimental study has been described in the literature as being reproducible and effective in illustrating processes that occur naturally in humans [13,14]. Thus, the observed transformations in the connective tissue matrix suggest that balanced nutrition represents a determining factor for establishing a good healing pattern.…”
Section: Discussionmentioning
confidence: 87%
“…The rats of both groups (M and N) were anesthetized with a mixture of ketamine and xylazine at the rate of 0.2ml/100 grams in weight. After performing trichotomy of the dorsal region with a razor blade, standardized cutaneous wounds [13,14] were made with a circular 8mm diameter scalpel (Biopsy Punch, Stiefel ® , Köln, Germany).…”
Section: Surgical Procedure Sacrifice and Histological Processingmentioning
confidence: 99%
“…Wound healing is a complex event that develops in three interrelated phases: inflammatory, proliferative and remodeling. In this process a dynamic interaction occurs between the extracellular matrix, growth factors, and cells [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%